Portrait d’un « fondateur dans l’âme » :: Clément Cormier, pionnier des sciences sociales en Acadie du Nouveau-Brunswick - Massicotte, Julien (Acadiensis, 2009)
Abstract In this article, the author seeks to establish the central role, often passed over in silence, played by Father Clément Cormier in the history of the social sciences in Acadia, particularly in the founding of a School of Social Sciences within the Collège Saint-Joseph in Memramcook. Father Cormier’s work stemmed in part from a plan to reproduce in Acadia, on a smaller scale, an institution similar to Father Georges-Henri Lévesque’s Faculty of Social Sciences at l’Université Laval. The article also underlines the role of the social sciences in the creation of an Acadian elite that was very active during the period of modernisation in the 1960s.